Integration of GPR and TLS for investigating the floor of the 'Salone dei Cinquecento' in Palazzo Vecchio, Florence, Italy. Issue 1 (26th June 2020) - Pieraccini, Massimiliano; Miccinesi, Lapo; Conti, Alessandro; Fiorini, Lidia; Tucci, Grazia; Pieri, Ilaria; Corazzini, Stefano
Abstract: Ground penetrating radar (GPR) is a powerful non‐destructive investigation tool widely used in archaeology. Its capabilities are greatly enhanced when it is operated in combination with a terrestrial laser scanner. This article reports on the radar investigation of the floor of Palazzo Vecchio's Great Hall. This monumental hall has been decorated by the most prominent artists of Italian Renaissance and it has radically changed at least twice since the 15th century. The aim of this investigation is to find features inside and under the floor that can contribute to a better reconstruction of the history of this monument. The main findings of this prospection have been the detection of a transversal girder not known on the south side of the Great Hall and a hemicycle structure under the floor. Both are probably remains of the works for adapting the hall to be used as the National Parliament of Italy between 1865 and 1870.